The Effect Of Common cold Massage To Reduce Cough Symptoms In Toddlers At Ramdani Husada Clinic - Febri Rosanti; Rosyidah Alfitri (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Common cold is an upper respiratory tract disorder that often occurs in infants and toddlers. This condition is caused by a viral infection, with rhinovirusas the most dominan etiologic agent. Treatment for common cold can be done through two main approaches, namely pharmacological and non-pharmacological. Pharmacological therapy involves of antipyretics such as paracetamol, and expectorans such as glyceryl guaicolate. On the other hand, non-pharmacological approache is a form of complementary therapy. One method used is common cold massage, which is claimed to provides a relaxing effect and help relieve respiratory symptoms through simulation at certain points. This study aims to determine the effect of common coldand cold symptoms in toddlers. This study uses a quantitative design with a quasi experimental. The sampling technique was carried out by purposive sampling. The sampling by purposive sampling, with a total of 22 toddlers as respondents. Data analysis was performed univarieately dan bivariately, using the Wilcoxon test to test the difference in symptom scores before and after the intervention. Pre-test data showed that 50%of respondents were in the sever cough and common cold category. After the intervention, the post-test results showed that 68,2% of toddlers decrease in to the mild category. The Wilcoxon test results showed a significance value of p = 0,000 (p = <0,005), which indicated thet there was a significant effect between common cold massage therapy and a decrease in cough and cold symptoms.